APRT deficiency: the need for early diagnosis. (23rd October 2018) - Huq, Aamira; Nand, Kushma; Juneja, Rajiv; Winship, Ingrid
Abstract : Adenine phosphoribosyltransferase (APRT) deficiency is a rare autosomal recessive disorder which leads to accumulation of poorly soluble 2, 8-dihydroxyadenine in kidneys resulting in nephrolithiasis as well as chronic kidney disease from crystal nephropathy. This report describes a 55-year-old previously fit man who presented with shortness of breath and the investigative pathway that eventually led to a diagnosis of APRT deficiency. Early diagnosis has aided in timely institution of allopurinol, thereby improving his renal function and possibility of weaning off renal replacement therapy. Genetic testing has enabled early identification of other family members at risk and prevention of renal failure by commencing xanthine oxidoreductase (XOR) inhibitors. The issues surrounding kidney donation by a member of this family are also discussed. This case represents the importance of awareness and recognition of the signs and symptoms of this rare condition, complications of which can be easily prevented by early institution of XOR inhibitor therapy.